Perceptions of selected urban poor Filipino households on sharing dwelling spaces in relation to domestic comfort a multiple case study - Vicuña, Yvette R.
This study was conducted to obtain the perceptions of selected urban poor Filipino households on sharing dwelling spaces in relation to domestic comfort. Sitio Palanas, an informal settlement in Quezon City, served as the locale of the study. Employing a multiple case study approach, nine cases were purposively selected from a sampling frame that resulted from the first phase of the study. The research methods used were direct observation of shared dwelling space/s and interview with the 27 participants, three representatives for each case. Rvbczynski's (1986) Onion Theory of Comfort, in which meanings of comfort are arranged in layers with the top layer being the most prioritized and the layers that are buried more deeply being given less importance, was used as a framework for analysis. The responses of the participants were validated using 11-point scale questionnaire. Considering the malleable definition of comfort, the results and findings of the study suggest that the selected participants perceived sharing of dwelling spaces as "tolerable or sufficient". Understanding such perceptions of the participants fills the gap between the increasing practice of sharing dwelling spaces among urban poor households and incorporating sharing of spaces as a feature of viable housing options specifically suitable for the marginalized group. As a recommendation, studies on sharing dwelling spaces with wider sampling range are encouraged to further affirm that such a housing arrangement can be incorporated in alternative socialized housing projects in urban areas.